2020
DOI: 10.1097/ceh.0000000000000321
|View full text |Cite|
|
Sign up to set email alerts
|

Journal Club Using Virtual Breakout Rooms: Interactive Continuing Education with No Learner Preparation During COVID-19

Abstract: Introduction: As a result of the COVID-19 pandemic, the authors rapidly transitioned an in-person, learner-led medical education journal club (MEJC) to the virtual environment. The “interactive, no-prep” approach, using breakout rooms within a videoconferencing system, required no prior learner preparation. Methods: From March to May 2020, learners were invited to participate in a monthly 60-minute virtual MEJC. A needs assessment survey informed articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…The authors found that, during the breakout groups, the learners produced perfectly effective study designs to answer the research question(s). Their results revealed that, as learners, they were well engaged in facilitated open discussion, and their learning outcomes were even [36].…”
Section: Breakout Groups and Language Learningmentioning
confidence: 99%
“…The authors found that, during the breakout groups, the learners produced perfectly effective study designs to answer the research question(s). Their results revealed that, as learners, they were well engaged in facilitated open discussion, and their learning outcomes were even [36].…”
Section: Breakout Groups and Language Learningmentioning
confidence: 99%
“…However, such didactic methods usually require participants to distantly watch and listen as passive learners without any interactivity [1]. In this context, there has been a shift in the educational paradigm from in-person to learner-led virtual ER environments [2] (the terms digital ERs and virtual ERs will be used interchangeably in our review and will serve as synonyms). Research has shown that millennials prefer informal learning experiences, such as ERs, due to their flexibility and because such activities engage and heighten students' interests [3].…”
Section: Introductionmentioning
confidence: 99%
“…Cadieux, et. al [9] have studied the impact of use of breakout rooms to train medical students with no prior training. They used a 60-minute virtual meeting of the Medical Education Journal Club (MEJC) to monitor around 15 participants.…”
Section: Related Workmentioning
confidence: 99%